2009
DOI: 10.1021/es8026659
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metabolites Formed During the Biotransformation of 17α-Ethinylestradiol by Nitrosomonas europaea in Batch and Continuous Flow Bioreactors

Abstract: The biotransformation of 17alpha-ethinylestradiol (EE2) by an ammonia oxidizing bacteria, Nitrosomonas europaea, grown in batch (ammonia-rich) and continuous flow (chemostat, ammonia-limited) reactors was investigated. Both C-14 labeled EE2 (10 gammag/L) and unlabeled EE2 (1 mg/L) were used to facilitate metabolite identification under environmentally relevant physiological conditions. Whole cell ammonia monooxygenase (AMO) activity was not inhibited at the EE2 concentrations used in this study. Characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 39 publications
1
42
0
1
Order By: Relevance
“…The biodegradation of EE2 in particular was examined by Skotnicka-Pitak et al [44] in continuous-flow experiments. Their EE2 loadings were c. 129.5 mg EE2 −1 kg N. europea tCOD d −1 , significantly higher than those of this study, 0.008-0.74 mg EE2 −1 kg AOB tCOD d −1 (mg EE2 biodegraded per kg of N. europea as tCOD per day) and biotransformation of EE2 was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biodegradation of EE2 in particular was examined by Skotnicka-Pitak et al [44] in continuous-flow experiments. Their EE2 loadings were c. 129.5 mg EE2 −1 kg N. europea tCOD d −1 , significantly higher than those of this study, 0.008-0.74 mg EE2 −1 kg AOB tCOD d −1 (mg EE2 biodegraded per kg of N. europea as tCOD per day) and biotransformation of EE2 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this research suggests that environmental concentrations of AOB and EE2 are insufficient to support co-metabolism during activated sludge treatment. Whilst it is postulated that the fortuitous activity of monoxygenase is important in the removal of organic contaminants such as trihalomethanes and chloroform [44,45], to date, evidence indicating that AOB can biotransform these chemicals at ng L −1 concentrations remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, laboratory-scale experiments are first performed at exaggerated concentrations to identify metabolites that form and persist. Although this is an accepted approach, microbial degradation of pharmaceuticals under different physiological conditions has been shown to produce different metabolites and therefore must be conducted with caution [71].…”
Section: Challenges In Metabolite Identification In the Environmentmentioning
confidence: 99%
“…Another study showed that the oxidative removal of trace organic contaminants correlated with the removal of ammonium (NH 4 + -N) [9]. Ammonia oxidizing bacteria (AOB) in the nitrifying activated sludge are able to degrade a range of aromatic compounds due to its nonspecific enzyme ammonium monooxygenase (AMO) [10,11], following cometabolism in the obligatory presence of a growth substrate such as ammonium [12]. AMO was capable of oxidizing a broad range of aromatic substrates [10,13], probably due to the mechanism of reaction with oxygenated form of AMO [14].…”
Section: Introductionmentioning
confidence: 99%